Pengembangan Tebing Keraton Sebagai Daya Tarik Wisata Alam di Kota Bandung - Gani, Abdul; Kemala, Zia; Sukriadi, Erie Hidayat (Manajemen dan Pariwisata, 2024)
Bandung is one of the cities in Indonesia that has various tourist destination. One of the flagship tourist destinations is Tebing Keraton, located in Ir. H. Djuanda Forest Park Area. Shortcomings in terms of planning, security, and development at Tebing Keraton encourage the needs of strategies and efforts to enhance its attractiveness. Therefore, this research aims to determine the conditions and development strategies of Tebing Keraton through the 5A concept. Method used in this research is qualitative descriptive with data collection through observation, interview, and documentation. Technique of analysis are data reduction, data presentation, and conclusion. Findings of the research show the tourism potential at Tebing Keraton that has fulfilled the principles of a tourist destination. First aspect is “something to see” through the view of natural landscapes, such as hills, pine forest, sunrise, and sunset view. Second aspect is “something to do” through its function as trekking and cycling route, camping area, and photography. Third aspect is “something to buy” with the presence of stalls around Tebing Keraton area. Development strategies to enhance tourism attractiveness are pursued through 5A Concept, Attraction, Accessibility, Accommodation, Amenities, and Activities, through maintenance and development of main and supporting facilities in the site area. Development strategies are aimed to increase its attractiveness and comfort, security, and safety for the tourists.